An assessment of the Egyptian government's use of public service announcements for development communication - El Marsafawy, Ghada (AUC Knowledge Fountain, 2019)
Mass media has long been used as a tool for communicating national development. It is through the use of public service announcements (PSAs) that nations could com-municate to the masses their development goals. This study examines the use of Pub-lic service announcements by the Egyptian government in order to communicate its 2030 development goals. A content analysis of television PSAs (N=69) has been con-ducted assessing the content and context of those PSAs comparing them to the crite-ria of effective PSAs. The categories analyzed in the PSAs were PSA Approach, PSA Message, PSA Appeal, PSA Source Characteristics, Personal Relevance, Message quality, Message understandability, Motivational incentives and Messenger attributes. Following the content analysis, in depth interviews were also conducted with experts in the fields of media, communication and development to gain richer information regarding the government's use of public service announcements in Egypt. Findings from the study have shown that while the content of the PSAs analyzed matched the criteria of effective PSAs, results from the interviews have showed that PSAs still did not have the required impact.